Functionalized degradable film with mechanical strength and natural oxidation resistance and preparation method thereof
By combining calcium carbonate-enhanced filler with carboxymethyl chitosan and artemisia granulate, the prepared films exhibit high mechanical strength and natural antioxidant properties in food preservation, solving the shortcomings of existing materials and achieving a green solution that is efficient in preservation and degradability.
Patent Information
- Application Number
- CN202510393106.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-01
AI Technical Summary
Existing food preservation materials are difficult to take into account high mechanical strength and natural oxidation resistance, and traditional plastic materials are difficult to degrade, which violates the concept of green development.
Calcium carbonate enhancement filler is used to combine with carboxymethyl chitosan and artemisia salina gel to prepare calcium carbonate nanoparticles loaded with rosemary acid by gas diffusion method to enhance the mechanical properties of the film and achieve slow release of antioxidants.
The prepared film has increased tensile strength by more than 3 times, has significant antioxidant and antibacterial properties, achieved a 15-day food preservation effect, and is biodegradable.
Smart Images

Figure CN120230327A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of membrane materials, relates to membrane materials for food packaging, and particularly relates to a functional degradable thin film with mechanical strength and natural antioxidant properties and a preparation method thereof. Background Art
[0002] Disclosing the information of this background art section is only intended to enhance the overall understanding of the present invention, and it is not necessarily regarded as an admission or an indication in any form that this information constitutes the prior art already known to those of ordinary skill in the art.
[0003] Traditional food preservation technologies, such as using petroleum-based plastic materials for preservation, not only have limited effects but also are difficult to degrade, which does not conform to the concept of green development; frozen preservation will damage the taste of food. These traditional preservation technologies generally have average effects, high costs, and most of them are not sustainable. Therefore, there is an urgent need for efficient natural food preservation materials in the market.
[0004] Carboxymethyl chitosan, as a chitosan derivative, has good antibacterial effects, but its mechanical properties are poor. Artemisia sphaerocephala gum is a natural macromolecular polysaccharide with excellent film-forming properties and biocompatibility.
[0005] Currently, many food packaging films on the market are difficult to balance mechanical properties and preservation effects, and people's requirements for food preservation materials are getting higher and higher. Therefore, it is necessary to invent a natural antioxidant film with high mechanical strength for food preservation. Summary of the Invention
[0006] To solve the deficiencies of the prior art, the purpose of the present invention is to provide a functional degradable thin film with mechanical strength and natural antioxidant properties and a preparation method thereof. The degradable thin film provided by the present invention simultaneously has properties such as high mechanical strength and natural antioxidant properties, which is beneficial to improving the food preservation effect.
[0007] To achieve the above purpose, the present invention provides the following technical solutions:
[0008] In the first aspect, a calcium carbonate enhanced filler, and its preparation method is: adding a calcium salt and rosmarinic acid to an aqueous alcohol solvent and mixing evenly to obtain a calcium solution, and using the calcium solution and NH4HCO3 as raw materials to prepare calcium carbonate nanoparticles loaded with rosmarinic acid through a gas diffusion method, which is the calcium carbonate enhanced filler.
[0009] The present invention adopts a gas diffusion method to decompose NH4HCO3 into NH3 and CO2, and the NH3 and CO2 are diffused into a calcium solution through gas to react and form calcium carbonate. During the reaction, the prepared calcium carbonate is porous due to the gas diffusion. At the same time, since the calcium solution contains rosmarinic acid, a part of the rosmarinic acid can be coated during the generation of calcium carbonate, and the prepared porous calcium carbonate can also load a part of the rosmarinic acid through the porous structure, thereby increasing the efficiency of loading the rosmarinic acid.
[0010] The calcium carbonate reinforced filler obtained by the preparation method of the present invention can not only be endowed with antioxidant properties, but also can prolong the antioxidant time by realizing multi-stage slow release of rosmarinic acid.
[0011] In a second aspect, a functionalized degradable film having mechanical strength and natural antioxidant properties comprises the following raw materials, calculated by weight: 100-130 parts of carboxymethyl chitosan, 30-50 parts of artemisia gum, and 10-20 parts of the above-mentioned calcium carbonate reinforcing filler.
[0012] Artemisia sphaerocephala gum is a natural macromolecular polysaccharide with excellent film-forming properties and biocompatibility. The present invention uses carboxymethyl chitosan and artemisia sphaerocephala gum as a base material for the film, which is conducive to maintaining its biodegradability and film-forming properties. Experiments have shown that adding the above-mentioned calcium carbonate reinforcing filler on the basis of the base material can significantly enhance the mechanical properties of the film material such as tensile strength, and its tensile strength can be increased by more than 3 times; it also has antioxidant properties.
[0013] In a third aspect, a method for preparing the above-mentioned functionalized degradable film is provided, comprising adding carboxymethyl chitosan and artemisia gum into water and mixing evenly, then adding the above-mentioned calcium carbonate reinforcing filler and mixing evenly, and then adding glycerol to prepare a film-forming liquid; and preparing a film from the film-forming liquid.
[0014] A fourth aspect is an application of the above functionalized degradable film in food fresh-keeping packaging.
[0015] The beneficial effects of the present invention are:
[0016] The present invention uses carboxymethyl chitosan and artemisia gum as the substrate of the film and adds calcium carbonate nanoparticles loaded with rosmarinic acid. The tensile strength of the composite film is significantly improved, which can reach more than 70MPa, indicating that the calcium carbonate nanoparticles loaded with rosmarinic acid can improve the mechanical strength of the film. Such particles can not only enhance its mechanical strength, but also have antioxidant properties due to the presence of rosmarinic acid, thereby realizing the preparation of a composite film integrating mechanical properties and antioxidant properties. The film is degradable and realizes the 15-day fresh-keeping of loquats. It has a good application prospect in the field of food fresh-keeping films and is expected to solve the effects of physical collision and oxidation on the freshness of fruits and vegetables during transportation. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings of the specification, which form a part of the present invention, are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention.
[0018] Figure 1 Electron microscope picture of CaCO3@Ra prepared in Example 1 of the present invention;
[0019] Figure 2 Fourier infrared spectrum of CaCO3@Ra prepared in Example 1 of the present invention;
[0020] Figure 3 Tensile strength and elongation at break of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0021] Figure 4 Stress-strain diagrams of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0022] Figure 5 Evaluation diagrams of antioxidant effects of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0023] Figure 6 Evaluation diagrams of antibacterial effects of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3;
[0024] Figure 7 Evaluation diagrams of the fresh-keeping effects of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3 on loquats;
[0025] Figure 8 Results diagrams of weight loss of fresh-keeping of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3 on loquats;
[0026] Figure 9 Diagrams of soil degradation of different film samples prepared in Example 1 of the present invention and Comparative Examples 1-3. Detailed Description of the Invention
[0027] It should be noted that the following detailed description is exemplary and is intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present invention belongs.
[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular forms are also intended to include the plural forms. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, they specify the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0029] In order to solve the problems of low mechanical strength and poor effect of delaying food spoilage existing in the existing natural food preservation materials, the present invention proposes a functional degradable film with mechanical strength and natural antioxidant properties and a preparation method thereof.
[0030] A typical embodiment of the present invention provides a calcium carbonate reinforced filler, and its preparation method is: adding a calcium salt and rosmarinic acid into an aqueous alcohol solvent and mixing evenly to obtain a calcium solution, and using the calcium solution and NH4HCO3 as raw materials to prepare calcium carbonate nanoparticles loaded with rosmarinic acid by a gas diffusion method, which is the calcium carbonate reinforced filler.
[0031] The calcium salt described in the present invention is a compound with a calcium ion as the cation, such as calcium chloride, calcium nitrate, etc.
[0032] In some embodiments, the mass ratio of the calcium salt to rosmarinic acid is 1.5 - 4.5:1.
[0033] In some embodiments, the mass ratio of the calcium salt to NH4HCO3 is 0.02 - 0.05:1.
[0034] The gas diffusion method adopted by the present invention is carried out in a dryer. In some embodiments, the conditions of the gas diffusion method are: the temperature is 35 - 55°C and the time is 20 - 50 hours. The temperature is preferably 40 - 50°C and the time is 22 - 26 hours.
[0035] Another embodiment of the present invention provides a functional degradable film with mechanical strength and natural antioxidant properties. Calculated by mass parts, it includes the following raw materials: 100 - 130 parts of carboxymethyl chitosan, 30 - 50 parts of artemisia sphaerocephala gum, and 10 - 20 parts of the above-mentioned calcium carbonate reinforced filler.
[0036] In some embodiments, it also includes 35 - 65 parts of glycerol.
[0037] A third embodiment of the present invention provides a preparation method of the above-mentioned functional degradable film. Add carboxymethyl chitosan and artemisia sphaerocephala gum into water and mix evenly, then add the above-mentioned calcium carbonate reinforced filler and mix evenly, and then add glycerol to make a film-forming solution; make the film-forming solution into a film.
[0038] In some embodiments, the temperature during the preparation process of the film-forming solution is 45 to 55 °C.
[0039] In some embodiments, the method for forming a film from the film-forming solution is the solution casting method.
[0040] The fourth embodiment of the present invention provides an application of the above functionalized degradable film in food fresh-keeping packaging.
[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific examples and comparative examples.
[0042] Example 1
[0043] (1) Preparation of calcium carbonate nanoparticles loaded with rosmarinic acid (CaCO3@Ra):
[0044] First, 150 mg of anhydrous calcium chloride was added to 80 mg of rosmarinic acid, and then 100 mL of anhydrous ethanol was added and stirred evenly. 300 μL of deionized water was added to the ethanol solution again and gently mixed, and then it was encapsulated in a desiccator together with another 5 g of NH4HCO3 and kept at a constant temperature of 40 °C for 24 hours. After the reaction was completed, it was centrifuged at a speed of 10,000 rpm for 10 minutes to remove the solvent, and then the precipitate was purified again at a speed of 6,000 rpm for 10 minutes to obtain pure CaCO3@Ra NPs. Then it was freeze-dried to obtain calcium carbonate nanoparticles loaded with rosmarinic acid.
[0045] (2) Preparation of the composite film:
[0046] 98.50 g of ultrapure water, 1.00 g of carboxymethyl chitosan, and 0.50 g of Artemisia sphaerocephala gum were weighed, heated to 50 °C and stirred evenly. After 30 minutes, 0.10 g of CaCO3@Ra nanoparticles were added and stirred evenly. After 20 minutes, 0.50 mL of glycerol was added and stirred evenly. After 20 minutes, 30 mL of this film-forming solution was taken and spread on a 90 mm petri dish. Finally, it was dried at 50 °C for 8 hours to obtain the CaCO3@Ra-carboxymethyl chitosan / Artemisia sphaerocephala gum composite film, denoted as CaCO3@Ra-SC.
[0047] Comparative Example 1
[0048] Preparation of carboxymethyl chitosan film:
[0049] Weigh 98.50 g of ultrapure water and 1.50 g of carboxymethyl chitosan, heat to 50 °C and stir evenly. After 30 minutes, add 0.50 mL of glycerol and stir evenly. After 20 minutes, take 30 mL of this film-forming solution and spread it in a 90-mm Petri dish. Finally, dry it at 50 °C for 8 hours to obtain the carboxymethyl chitosan film, denoted as CMCS.
[0050] Comparative Example 2
[0051] Preparation of the artemisia sphaerocephala Krasch gum film:
[0052] Weigh 98.50 g of ultrapure water and 1.50 g of artemisia sphaerocephala Krasch gum, heat to 50 °C and stir evenly. After 30 minutes, add 0.50 mL of glycerol and stir evenly. After 20 minutes, take 30 mL of this film-forming solution and spread it in a 90-mm Petri dish. Finally, dry it at 50 °C for 8 hours to obtain the artemisia sphaerocephala Krasch gum film, denoted as SSG.
[0053] Comparative Example 3
[0054] Preparation of the composite film:
[0055] Weigh 98.50 g of ultrapure water, 1.00 g of carboxymethyl chitosan, and 0.50 g of artemisia sphaerocephala Krasch gum, heat to 50 °C and stir evenly. After 30 minutes, add 0.50 mL of glycerol and stir evenly. After 20 minutes, take 30 mL of this film-forming solution and spread it in a 90-mm Petri dish. Finally, dry it at 50 °C for 8 hours to obtain the carboxymethyl chitosan / artemisia sphaerocephala Krasch gum composite film, denoted as SC.
[0056] It can be seen from Figure 1 that scanning electron microscopy (SEM) shows that CaCO3 has a spherical structure, and its surface forms a coating layer due to the coverage of rosmarinic acid. It can be seen from Figure 2 that rosmarinic acid is loaded into calcium carbonate. Transmission electron microscopy (TEM) clearly observes the porous structures of CaCO3 and CaCO3@Ra: the boundary of CaCO3 is clear, while the boundary of CaCO3@Ra is relatively blurred, confirming that rosmarinic acid is loaded on the surface of porous CaCO3. In addition, the loading efficiency of rosmarinic acid on CaCO3 is 39.64 ± 0.04%, which is higher than the level of similar studies.
[0057] It can be seen from Figure 3 and Figure 4 that the addition of calcium carbonate nanoparticles loaded with rosmarinic acid significantly improves the tensile stress of the film, increasing it by nearly 3 times, endowing the film material with excellent mechanical properties.
[0058] The antioxidant properties of the film samples were evaluated by the DPPH and ABTS radical scavenging rates. As Figure 5 shown, after adding calcium carbonate nanoparticles loaded with rosmarinic acid, the antioxidant ability of the film has been significantly improved.
[0059] The antibacterial properties of the film were evaluated by the plate counting method. The CaCO3@Ra-carboxymethyl chitosan / artemisia sphaerocephala gum composite film had excellent antibacterial properties. As Figure 6 can be seen, there were no colonies on the plates of this sample group.
[0060] The film samples were coated on the surface of loquats for preservation. The loquats after different preservation times were photographed. The results are as Figure 7 and Figure 8 shown. The Control group was the group of loquats without the film samples covered. They lost a lot of water during storage and the epidermis was wrinkled. The carboxymethyl chitosan film could ensure that the loquats did not rot for 9 days, thus achieving 9-day preservation. The preservation time of the artemisia sphaerocephala gum film was less than 3 days. The carboxymethyl chitosan / artemisia sphaerocephala gum composite film could achieve 12-day preservation. The CaCO3@Ra-carboxymethyl chitosan / artemisia sphaerocephala gum composite film could achieve more than 15-day preservation of loquats.
[0061] The film samples were placed in the soil for degradation. The results are as Figure 9 shown. CMCS had the fastest degradation rate because of its simple structure and no macromolecular entanglement. SSG completely disappeared after 9 days. SC and CaCO3@Ra-SC were partially degraded, which might be attributed to the macromolecular entanglement and hydrogen bond interaction delaying the degradation process. These materials were all biodegradable and in line with the concept of green development.
[0062] Example 2
[0063] (1) Preparation of calcium carbonate nanoparticles loaded with rosmarinic acid (CaCO3@Ra):
[0064] First, 180 mg of anhydrous calcium chloride was added to 40 mg of rosmarinic acid, and then 100 mL of anhydrous ethanol was added and stirred evenly. 300 μL of deionized water was added to the ethanol solution again and gently mixed. Subsequently, it was encapsulated in a desiccator together with another 6 g of NH4HCO3 and kept at a constant temperature of 50 °C for 24 hours. After the reaction was completed, it was centrifuged at a speed of 10000 rpm for 10 minutes to remove the solvent, and then the precipitate was purified again at a speed of 6000 rpm for 10 minutes to obtain pure CaCO3@Ra NPs. Then it was freeze-dried to obtain the calcium carbonate nanoparticles loaded with rosmarinic acid.
[0065] (2) Preparation of the composite film:
[0066] Weigh 98.50 g of ultrapure water, 1.00 g of carboxymethyl chitosan, and 0.50 g of Artemisia sphaerocephala gum, heat to 50 °C and stir evenly. After 30 minutes, add 0.10 g of CaCO3@Ra nanoparticles and stir evenly. After 20 minutes, add 0.50 mL of glycerol and stir evenly. After 20 minutes, take 30 mL of this film-forming solution, spread it on a 90 mm Petri dish. Finally, dry it at 50 °C for 8 hours to obtain the CaCO3@Ra-carboxymethyl chitosan / Artemisia sphaerocephala gum composite film.
[0067] Example 3
[0068] (1) Preparation of calcium carbonate nanoparticles loaded with rosmarinic acid (CaCO3@Ra):
[0069] First, add 150 mg of anhydrous calcium chloride to 80 mg of rosmarinic acid, then add 100 mL of anhydrous ethanol and stir evenly. Add 300 μL of deionized water to the ethanol solution again and mix gently, then encapsulate it with another 5 g of NH4HCO3 in a desiccator and keep it at a constant temperature of 35 °C for 48 hours. After the reaction is completed, centrifuge at a speed of 10000 rpm for 10 minutes to remove the solvent, and then purify the precipitate again at a speed of 6000 rpm for 10 minutes to obtain pure CaCO3@Ra NPs. Then freeze-dry it to obtain calcium carbonate nanoparticles loaded with rosmarinic acid.
[0070] (2) Preparation of the composite film:
[0071] Weigh 98.50 g of ultrapure water, 1.30 g of carboxymethyl chitosan, and 0.3 g of Artemisia sphaerocephala gum, heat to 45 °C and stir evenly. After 30 minutes, add 0.20 g of CaCO3@Ra nanoparticles and stir evenly. After 20 minutes, add 0.30 mL of glycerol and stir evenly. After 20 minutes, take 30 mL of this film-forming solution, spread it on a 90 mm Petri dish. Finally, dry it at 45 °C for 8 hours to obtain the CaCO3@Ra-carboxymethyl chitosan / Artemisia sphaerocephala gum composite film.
[0072] The above are only the preferred embodiments of the present invention and are not used to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A calcium carbonate reinforcing filler, characterized in that: The preparation method is as follows: calcium salt and rosmarinic acid are added to an aqueous alcohol solvent and mixed evenly to obtain a calcium solution; the calcium solution and NH4HCO3 are used as raw materials through a gas diffusion method to prepare rosmarinic acid-loaded calcium carbonate nanoparticles, namely, calcium carbonate reinforcing fillers.
2. The calcium carbonate reinforcing filler according to claim 1, characterized in that: The mass ratio of calcium salt to rosmarinic acid is 1.5-4.5:
1.
3. The calcium carbonate reinforcing filler as claimed in claim 1, characterized in that: The mass ratio of calcium salt to NH4HCO3 is 0.02-0.05:
1.
4. The calcium carbonate reinforcing filler according to claim 1, characterized in that: The conditions of the gas diffusion method are: temperature of 35 to 55°C and time of 20 to 50 hours.
5. A functionalized degradable film having mechanical strength and natural antioxidant properties, characterized in that: The raw materials are comprised of the following materials in parts by mass: 100-130 parts of carboxymethyl chitosan, 30-50 parts of artemisia gum, and 10-20 parts of the above-mentioned calcium carbonate reinforcing filler.
6. The functionalized degradable film according to claim 5, characterized in that: The composition also includes 35 to 65 parts of glycerin.
7. A method for preparing the functionalized degradable film according to claim 5, characterized in that: Carboxymethyl chitosan and artemisia gum are added into water and mixed evenly, then the calcium carbonate reinforcing filler is added and mixed evenly, and then glycerol is added to prepare a film-forming liquid; and the film-forming liquid is prepared into a film.
8. The preparation method according to claim 7, characterized in that: The temperature of the film-forming solution preparation process is 45-55°C.
9. The preparation method according to claim 7, characterized in that: The method of making the membrane from the membrane-forming liquid is solution casting.
10. Use of the functionalized degradable film according to claim 5 or 6 in food fresh-keeping packaging.